America's godly heritage - Barton, David; WallBuilders (Organization); Vision Video (Firm) (Worcester, PA : Distributed by Vision Video, 1992)
Presents an interpretation of the beliefs of the Founding Fathers of the United States concerning the role of Christian principles in education and government; provides excerpts from court cases showing that for 160 years Christian principles were officially and legally inseparable from American public life and shows what has happened since the courts have rejected the Founder's beliefs.
DVD format.
Presenter, David Barton.
Keywords: Church and state -- United States -- History; Freedom of religion -- United States -- History; Christianity and politics; Democracy -- Religious aspects -- Christianity; Religion in the public schools; Christianity -- United States -- Philosophy; United States -- History -- Philosophy; Documentary videos; Religious videos